Stock Market Effects of the Closeness to Debt Covenant Restrictions Resulting from Capitalization of Leases. - El-Gazzar, Samir M. (The Accounting Review, 1993)
This article examines the association between lessees' market returns and their changes in the tightness of the debt covenant constraints resulting from compliance with SFAS No. 13 (1976). This paper differs from previous research in that it uses covenant-based measures. Similar to Hughes and Ricks (1984) and Schipper and Thompson (1983), it examines cross-sectional stock return dependencies that exist when industry effects cannot be randomized over time. The paper begins by identifying a sample of lessees who retroactively capitalized leases as a result of SFAS No. 13. Actual debt contracts of same pie firms are then analyzed to identify accounting-based restrictions, the default value of each restriction, and the definition of the accounting variables used in the covenant. Next, the percentage increase in the tightness of covenant restrictions arising from adopting SFAS No. 13 is calculated. Finally, cross-sectional tests of the relationship between changes in covenant tightness and changes in security prices that accompanied the events leading to SFAS No. 13 are performed. The analyses reveal several results. First, retroactive capitalization of off-balance sheet leases would have caused significant increases in the tightness of the debt covenant restrictions. Second, affected lessees experienced negative market returns contemporaneously with the disclosure of two of the events that led to the promulgation of SFAS No. 13. However, the magnitude of the reduction in market returns is correlated with the impact of SFAS No. 13 on the tightness of debt covenant restrictions. Finally, there appear to be important differences in the structure of debt covenants. Private debt covenants have tighter financial restrictions, while public debt covenants have more nonaccounting-based provisions such as sinking fund, security, and seniority of the debt.